Pengaruh Capital Adequacy Ratio, Loan to Deposit Ratio, Non Performing Loan terhadap Profitabilitas - Lestari, Hani Fitri; Ernawan, Yana; Nusannas, Iman Sidik (The Double Entry Journal, 2022)
This research aims to determine the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL) on Profitability (ROA). Data observation used in banking companies listed on the Indonesia Stock Exchange, with total 10 samples for the period 2012 – 2016. Technique analysis using multiple linear regression, and using classic assumption test for data eligibility test. This result indicates that Capital Adquecy Ratio (CAR) and the Loan to Deposit Ratio (LDR) does not have a significant effect on Profitability (ROA). Meanwhile, Non Performing Loans (NPL) have a negative significant effect on Profitability (ROA).